Effect of Cu2+ ions doped on the photovoltaic features of CdSe quantum dot sensitized solar cells. (20th August 2018) - Nguyen, Tan Phat; Ha, Thanh Tung; Nguyen, Thu Thao; Ho, Nhat Phuong; Huynh, Thanh Dat; Lam, Quang Vinh
Abstract: In this paper, we have succeeded in preparing the Quantum dots Solar cells with the high efficiency of 4.22% based on Cu 2+ ions doped on CdSe Quantum dots by Successive ionic layer absorption and reaction. There are significant effects of Cu 2+ ions on optical, physical, chemical and photovoltaic features of QDSSCs. As a result, the current density of the QDSSCs increased dramatically from 12 mA/cm 2 for pure CdSe QDs to 19.915 mA/cm 2 for Cu 2+ ions doped on pure CdSe QDs. In fact, Cu 2+ dopant rise in the conduction band of pure CdSe QDs, reduces recombination, enhances the efficiency of high harvesting, improve the charge transfer and collection. In addition, Cu 2+ dopant raise the level of the conduction band of pure CdSe QDs, which leads to reduce the charge recombination, enhance the light-harvesting efficiency and improve the charge diffusion and collection. In the same way, we also illustrated photoluminescence decay to determine the lifetime of excited electrons and Electrochemical Impedance Spectra to calculate dynamic resistances in QDSSCs and explain the obtained results.